METAPHORS OF SOCIAL JUSTICE IN DIGITAL DISCOURSE: IDENTITY CONSTRUCTION AND MINORITY VOICES IN INDONESIA’S PROTESTS - Mahmudah Mahmudah; Suriadi Suriadi; Filawati Filawati (Jurnal Gramatika, 2026)
Social justice protests in digital discourse increasingly rely on metaphor to articulate political demands, construct collective identity, and amplify marginalized voices. However, limited research has examined how metaphors function as ideological tools in postcolonial protest discourse, particularly in Indonesia. Addressing this gap, this study critically analyzes social justice metaphors circulating in Indonesian digital protests from August to September 2025 to explore how language constructs political identity and represents minority voices. Drawing on Teun A. van Dijk’s Critical Discourse Analysis framework, this qualitative study examines seventeen widely circulated protest texts from social media platforms. The analysis integrates textual structure, social cognition, and socio-political context to identify dominant metaphorical patterns and their ideological functions. The findings reveal five major metaphor categories: spatial power, institutional justice, moral, economic justice, coercive, repressive state, and democratic solidarity. These metaphors function to delegitimize state coercion, frame social inequality as a moral crisis, and construct “the people” as ethical political actors. Importantly, metaphors of solidarity and justice provide discursive space for marginalised groups, such as workers, students, and victims of state violence, to assert their legitimacy in the public sphere. This study argues that metaphors in digital protest discourse operate not merely as rhetorical devices but as instruments of resistance that challenge dominant power structures and reconfigure political identity. By foregrounding Indonesia’s postcolonial context, the research extends critical metaphor studies beyond Western-centric analyses and highlights the role of digital discourse in shaping contemporary democratic struggles. Future research is encouraged to adopt multimodal and comparative approaches to explore further the relationship between metaphor, ideology, and minority representation in global protest movements.